Research progress of GLP-1RAs in the treatment of type 2 diabetes mellitus - He, Xu; Zhao, Wei; Li, PeiHang; Zhang, YinJiang; Li, GuoHua; Su, HongYu; Lu, BiNan; Pang, ZongRan (Frontiers in Pharmacology, 2025)
Glucagon-like peptide-1 (GLP-1) is a 30-amino acid intestinal insulin-stimulating factor, which is mainly secreted by L cells in the distal ileum and colon. It has various physiological functions, such as promoting insulin secretion and synthesis, stimulating β-cell proliferation, inducing islet regeneration, inhibiting β-cell apoptosis and glucagon release, delaying gastric emptying and controlling appetite, etc. It plays a role through a specific GLP-1 receptor (GLP-1R) distributed in many organs or tissues and participates in the regulation of glucose homeostasis in the body. GLP-1 receptor agonists (GLP-1RAs) has the similar physiological function of GLP-1. Because of its structural difference from natural GLP-1, it is not easy to be degraded by dipeptidyl peptidase-4 (DPP-4), thus prolonging the action time. GLP-1RAs have been recognized as a new type of hypoglycemic drugs and widely used in the treatment of type 2 diabetes mellitus (T2DM). Compared with other non-insulin hypoglycemic drugs, it can not only effectively reduce blood glucose and glycosylated hemoglobin (HbA1c), but also protect cardiovascular system, nervous system and kidney function without causing hypoglycemia and weight gain. Therefore, GLP-1RAs has good application prospects and potential for further development.